Influence of Democratic Leadership and Performance Management on Organizational Commitment Through Employee Awards at the Sungai Penuh City Environmental Service - Fetra Handika; Heryanto (Jurnal Informatika Ekonomi Bisnis, 2026)
This study aims to analyze the influence of Democratic Leadership and Performance Management on Organizational Commitment through Rewards as a mediating variable in the employees of the Sungai Penuh City Environmental Service. This study uses a quantitative approach with a survey method. The population in this study were all employees of the Sungai Penuh City Environmental Service with a sample of 34 respondents, determined using a saturated sampling technique. Data collection was carried out through questionnaires, while data analysis used multiple linear regression analysis, path analysis, and the Sobel Test, with the help of the IBM SPSS version 26 program. The results of the study indicate that Democratic Leadership and Performance Management have a positive and significant effect on Rewards. In addition, Democratic Leadership and Performance Management also have a positive and significant effect on Organizational Commitment. However, Rewards do not have a significant effect on Organizational Commitment. The results of the path analysis and the Sobel Test indicate that Rewards are unable to mediate the influence of Democratic Leadership and Performance Management on Organizational Commitment. The conclusion of this study is that the Organizational Commitment of the Sungai Penuh City Environmental Service employees is more directly influenced by Democratic Leadership and Performance Management, while Rewards play a supporting factor, but have not been able to become a determining factor or mediating variable. This research is expected to provide practical contributions to agencies in increasing employee organizational commitment by strengthening democratic leadership and improving performance management systems.